Behavioral investigation of reactive and neoplastic lymphocytes in human lymph nodes in 4D - Diana Elisa Theil; Cornelius Bütow; Sonja Scharf; Hendrik Schäfer; Sylvia Hartmann; Martin-Leo Hansmann; Patrick Wurzel (PLoS ONE, 2025)
This study deals with a 4D investigation of lymphocytes in human tissue under reactive and neoplastic conditions. The immune system’s response to pathogens highly depends on cell interaction and movement, which makes it essential to analyze these dynamics. To achieve this, we observed cells and their movement in 4D. Human lymphoid tissue was examined, including 8 cases with 23 movies of hyperplastic tissue from the pharyngeal tonsil and 12 cases with 35 movies of lymphadenitis. Additionally, there were 4 cases involving 16 movies of marginal zone lymphoma (MZL), 3 cases with 19 movies of nodular lymphocyte predominant Hodgkin lymphoma (NLPHL), 3 cases with 6 movies of follicular lymphoma grade 1/2 (FL), and 2 cases with 10 movies of diffuse large B-cell lymphoma (DLBCL). We tracked the movement, analyzed the activity of B cells and PD1-positive T cells under reactive conditions, and compared the results to different types of lymphomas. In this study, CD20-positive B cells were examined in the context of CD35 staining. CD35 stains follicular dendritic cells (FDC), an indication for a germinal center, so we primarily analyzed B cells in the germinal center areas and partially in the immediate periphery. We categorized cells by defining track types (Low motion cells, Moving and turning in place, Long distance movement) to describe their movement pattern and action types (Passive cells, Interactive cells, Active cells) to describe their behavior and interactions. In neoplastic tissue, slower cellular dynamics and fewer interactions were observed compared to reactive tissue. This indicates differences in cellular behavior between reactive and neoplastic tissues, with a more dynamic cellular environment observed in reactive tissue.